Alice's adventures in Wonderland & through the looking-glass - Carroll, Lewis, 1832-1898; Cohen, Morton N. (New York : Bantam Classic, 2006)
Two classic fantasy stories follow the adventures of Alice in a whimsical world and through a mirror, accompanied by an introduction providing historical context and literary analysis.
Includes bibliographical references and notes.
Keywords: Fantasy fiction; Wonderland (Imaginary place) -- Fiction; Juvenile literature; Satire -- Fiction